(untitled) (World Bulletin of Education and Learning, 2025)
Sports and creativity play a crucial role in reducing stress in children. They not only help them relax and develop physical and emotional skills but also serve as effective means of self-expression and coping with inner struggles. Parents and teachers can create conditions for these activities to become regular and beloved by children, helping them cope more easily with life’s challenges.